Application of a statcom to improve voltage stability in a grid connected wind turbine - Truong , Đình Nhơn; Nguyen , Văn Trí (Journal of Technical Education Science, 2022)
This paper presents the application of a static synchronous compensator (STATCOM) to improve stability of wind power voltage using doubly-fed induction generator (DFIG)-based wind turbine connected to power grid. The studied system consists of a 14-bus system and 6-MW wind power system of including three 2-MW DFIG generators connected to 13.8 kV bus of the power system. The simulation results derived in MATLAB software showed that the impact of the proposed STATCOM can truly enhance the stability of the studied system.